Which factors determine the grades of undergraduate students in economics? Some evidence from Spain - Juan José Dolado; Eduardo Morales (Institute for the Study of Labor (IZA), 2006)
This paper analyses the determinants of grades achieved in three core subjects by first-year Economics undergraduate students at Universidad Carlos III de Madrid, over the period 2001-2005. Gender, nationality, type of school, specialization track at high school and the grades at the university entry exam are the key factors we examine. Our main findings are that those students who did a technical track at high school tend to do better in mathematics than those who followed a social sciences degree and, that the latter do not perform significantly better than the former in subjects with less degree of formalism and more economic content. Moreover, students from public schools are predominant in the lower (with social sciences or humanities tracks) and upper (with a technical track) parts of the grade distribution, and females tend to perform better than males
urn:nbn:de:101:1-20080509234
Keywords: 330; Bildungsniveau; Hochschule; Wirtschaftsstudium; Qualifikation; Spanien